A Fatal Case of Naegleria fowleri Meningoencephalitis in Taiwan - Su, Mei-Yu (The Korean Society for Parasitology and Tropical Medicine, 2013)
After bathing at a hot spring resort, a 75-year-old man presented to the emergency department because of seizure-like attack with loss of conscious. This is the first case of primary amebic meningoencephalitis (PAM) caused by Naegleria fowleri in Taiwan. PAM was diagnosed based on detection of actively motile trophozoites in cerebrospinal fluid using a wet-mount smear and the Liu's stain. The amoebae were further confirmed by PCR and gene sequencing. In spite of administering amphotericin B treatment, the patient died 25 days later.